2021
DOI: 10.5194/soil-7-83-2021
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotope signatures of soil nitrogen on an environmental–geomorphic gradient within the Congo Basin

Abstract: Abstract. Nitrogen (N) availability can be highly variable in tropical forests on regional and local scales. While environmental gradients influence N cycling on a regional scale, topography is known to affect N availability on a local scale. We compared natural abundance of 15N isotopes of soil profiles in tropical lowland forest, tropical montane forest, and subtropical Miombo woodland within the Congo Basin as a proxy to assess ecosystem-level differences in N cycling. Soil δ15N profiles indicated that N cy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…We suggest that this increase in foliar δ 15 N in the nutrientrich pots can be explained by greater opportunity for N loss from the pots by δ 15 N fractionating pathways than in the case where nutrient availability is low and available N is effectively captured by the soil-plant system. In support of this, we also observed that foliar δ 15 N varied as a function of root mass (Supplementary Figure 7), indicating the influence of larger root systems in capturing available nitrogen, thereby limiting loss pathways from the soil-plant system that would otherwise leave the residual δ 15 N in the system 15 N enriched (Baumgartner et al, 2021).…”
Section: Foliar δ 15 N and Elevationsupporting
confidence: 67%
See 1 more Smart Citation
“…We suggest that this increase in foliar δ 15 N in the nutrientrich pots can be explained by greater opportunity for N loss from the pots by δ 15 N fractionating pathways than in the case where nutrient availability is low and available N is effectively captured by the soil-plant system. In support of this, we also observed that foliar δ 15 N varied as a function of root mass (Supplementary Figure 7), indicating the influence of larger root systems in capturing available nitrogen, thereby limiting loss pathways from the soil-plant system that would otherwise leave the residual δ 15 N in the system 15 N enriched (Baumgartner et al, 2021).…”
Section: Foliar δ 15 N and Elevationsupporting
confidence: 67%
“…Foliar δ 15 N has been observed to decrease with increasing elevation in tropical rainforest trees (Bauters et al, 2017). This is thought to be the result of more open N cycling at warm, low elevations, and with tighter N cycling at higher elevations as a result of slower N mineralization rates caused by low temperatures and less decomposable litter (Martinelli et al, 1999;Baumgartner et al, 2021). More open N cycling feeds N loss pathways from the ecosystem that tend to leave the residual N pool relatively enriched in 15 N (Martinelli et al, 1999;Craine et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Geographical coverage was improved by adding a further 748 samples 85 88 , including unpublished data for 112 samples from Australia (BASE database; 89 ) and 392 from Africa (experimental sites and set up described in refs. 90 96 )—regions which were underrepresented in the Craine database. The majority of data was from near-surface soil (0–50 cm depth).…”
Section: Methodsmentioning
confidence: 99%
“…All told, interpreting soil nitrogen isotope levels to describe N availability is challenging due to the many factors that influence its value. But overall, it shows the turnover of the nitrogen cycle: higher levels are more prone to N losses and lower values refer to more closed N systems where soil holds the nitrogen more ( Baumgartner et al, 2021 ). Roughly, 15 N can be used as a measure describing nitrogen availability for plants.…”
Section: Discussionmentioning
confidence: 99%